Corporate governance, financial institutions and the "social licence". Issue 3 (2nd July 2016) - Hanrahan, Pamela
Abstract : Financial institutions owe a range of obligations – legal and regulatory, contractual, and non-legal – to their shareholders, their other stakeholders and, arguably, to the public good. Understanding the nature and intensity of those obligations, and the role of boards in balancing and reconciling them, is a key concern of corporate governance. Recent discussions about the need for financial sector entities to earn and maintain a social licence to operate suggest a new way of framing discussions about these obligations.